The Effectiveness Extensive Reading Strategy on the Students’ Ability in Reading Comprehension - Mohammad Arief Wahyudi; Ihwan Firmansyah (Departement of Mathematics Education, 2023)
The real research was The Effectiveness Extensive Reading Strategy on the students’ ability in reading comprehension was conducted at The Fifth Semester Students of STKIP PGRI Bangkalan as subject because they have gotten some problem to comprehend the text in Extensive Reading course. In solving their problem, the researcher tried to overcome by introducing Extensive Reading Strategy, because Extensive Reading is one of the strategies that can used to teach vocabulary and extensive reading can enhance student vocabulary, it needs the process of extensive reading in order that students can read more and more. The research was done from Jan 2nd to April15th2023. The population of The Fifth Semester Students in academic year 2020/2021 was 30 students, which consists one classroom. One class were taken as the sample of this research. The experimental quantitative research was applied in this research. The quantitative design, researcher used one class to be experimental group and control groups. The facts showed that T- critical (T- c) value was higher than the t-table on the level 2.024. Therefore, the null hypothesis was rejected and alternative hypothesis was accepted. So, the researcher concluded the alternative was accepted that there was any significant Effectiveness Extensive Reading Strategy on the students’ ability in reading comprehension. The students difficulties of using the Extensive Reading Strategy on the students’ ability based on the minimal passing grade the students that 30 points or 30% was low did not get pass the minimal passing grade and the students got above passed of the minimal passing grade 70%, it means that there was The Effective Extensive Reading Strategy on the students’ ability in reading comprehension was succeeded.